Management of intertrochanteric fracture in a bilateral below knee amputee - Rao, Sneha Nagesh; Iyengar, Rajkumar (International Journal of Research in Orthopaedics, 2019)
Intertrochanteric fracture in a patient with bilateral below knee amputation is rare and the management is challenging. The major difficulty is in applying optimal amount of traction for reduction of the fracture due to absence of foot. We present the case of an elderly female with bilateral below knee amputation presenting with a minimally displaced right intertrochanteric fracture. The patient was managed using reverse boot technique for applying traction, obtaining reduction and fixed with right proximal femoral nail. The patient was able to return to her pre-injury mobility status on the third postoperative day. We highlight a method of traction application using this simple modification of the fracture table so that adequate amount of traction can be applied safely.